Leaps of faith : stories from working-class scholars - Benoit, Anne C.; Olson, Joann S.; Johnson, Carrie, 1955- (Emerald Publishing Limited : Information Age Publishing, Inc., 2019)
As discourses and programming to support diversity and inclusion across higher education are intensifying, Leaps of Faith: Stories from Working-Class Academics presents a collection of narratives that highlights the "on-the-ground" experiences of working-class students and scholars. These are stories of negotiation, transition, and challenge. These are stories of struggle. These are stories of beating the odds.The early works of Ryan and Sackrey (1984), Sennett and Cobb (1993), and Dews and Law (1996) raised the voices of working-class academics, and the subject of class in higher education has gained traction--especially with the increasing focus on the enrollment and persistence of first-generation college students. This project situates contributor stories in adult learning and development, with the goal of enhancing dialogue and increasing understanding of a still-hidden population in the academy. Leaps of Faith: Stories from Working-Class Academics is a compelling collection of reflections from working-class students and scholars from diverse demographic and geographic backgrounds who are currently navigating various transition points and career stages.Leaps of Faith: Stories from Working-Class Academics presents the strengths and gifts of the scholar-contributors and the opportunity to "turn the stories" through accessible and meaningful reflective "telling." The collection concludes with a discussion of salient implications for working-class students and scholars, those who support their learning and development, and higher education institutions and programs.
Keywords: Working class -- Education (Higher) -- United States.; Learning and scholarship -- Social aspects -- United States.; College teachers -- United States -- Biography.; Scholars -- United States -- Biography.; elektronické knihy; Biographies.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; electronic books